2020
DOI: 10.1016/j.molp.2020.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Transcriptional Regulation by the UV-B Photoreceptor and Multiple Transcription Factors for Plant UV-B Responses

Abstract: Non-damaging ultraviolet B (UV-B) light promotes photomorphogenic development and stress acclimation through UV-B-specific signal transduction in Arabidopsis. UV-B irradiation induces monomerization and nuclear translocation of the UV-B photoreceptor UV RESISTANCE LOCUS 8 (UVR8). However, it is not clear how the nuclear localization of UVR8 leads to changes in global gene expression. Here, we reveal that nuclear UVR8 governs UV-B-responsive transcriptional networks in concert with several previously known tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 56 publications
(69 reference statements)
1
68
0
Order By: Relevance
“…We speculate that these genes may be related to the developmental regulation and ecological adaptability of the two subpopulations. For instance, UV-B light and the abscisic acid receptor PYL8 can regulate cotyledon root development and stress adaptation by MYB13 interaction (Zhao et al, 2014b;Qian et al, 2020). The abscisic acid receptor PYL9 improves drought resistance by regulating leaf senescence (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that these genes may be related to the developmental regulation and ecological adaptability of the two subpopulations. For instance, UV-B light and the abscisic acid receptor PYL8 can regulate cotyledon root development and stress adaptation by MYB13 interaction (Zhao et al, 2014b;Qian et al, 2020). The abscisic acid receptor PYL9 improves drought resistance by regulating leaf senescence (Zhao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…UV-B is sensed by the photoreceptor UVR8, which activates the transcription factor HY5; then, HY5 up-regulates the expression of the transcription factors that control the biosynthesis of flavonoids and anthocyanins (Brown et al, 2005;Stracke et al, 2010;Tohge et al, 2011;Shin et al, 2013). In addition, it has been shown that UVR8 binds directly to the transcription factor MYB13 regulating flavonoid biosynthesis in a UV-B-dependent manner (Qian et al, 2020). Among the members in MBW complexes, at least MYB12, MYB111, MYB75, MYB13 and GL3 have been shown to be induced by UV-B (Brown et al, 2005;Stracke et al, 2010;Tohge et al, 2011;Yan et al, 2012;Qian et al, 2020).…”
Section: Narrowband Uv-b Irradiation Does Not Induce Flavonoid Biosynmentioning
confidence: 99%
“…In addition, it has been shown that UVR8 binds directly to the transcription factor MYB13 regulating flavonoid biosynthesis in a UV-B-dependent manner (Qian et al, 2020). Among the members in MBW complexes, at least MYB12, MYB111, MYB75, MYB13 and GL3 have been shown to be induced by UV-B (Brown et al, 2005;Stracke et al, 2010;Tohge et al, 2011;Yan et al, 2012;Qian et al, 2020). In this study HY5, MYBL2, and TTG1 were significantly up-regulated, and HYH and MYB12 also tended to be up-regulated by both 280 and 310 nm UV-LED irradiation.…”
Section: Narrowband Uv-b Irradiation Does Not Induce Flavonoid Biosynmentioning
confidence: 99%
See 1 more Smart Citation
“…The COP1 substrate ELONGATED HYPOCOTYL 5 (HY5), a crucial positive regulator of light signaling (Osterlund et al, 2000), is induced transcriptionally and stabilized post-transcriptionally, and is necessary for the regulation of most UVR8-induced genes (Ulm et al, 2004;Brown et al, 2005;Oravecz et al, 2006;Favory et al, 2009;Huang et al, 2012;Binkert et al, 2014). Additionally, UVR8 regulates the stability or DNA-binding activity of a set of transcription factors affecting UV-B responses (Hayes et al, 2014;Liang et al, 2018;Yang et al, 2018;Sharma et al, 2019;Qian et al, 2020;Tavridou et al, 2020a;Tavridou et al, 2020b;Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%